Back to Linnaeus: Proper Botanical Naming of the Tetraploid Indian Acorus (Acoraceae), an Important Medicinal Plant - Dmitry D. Sokoloff; Margarita V. Remizowa; Mikhail V. Skaptsov; Shrirang R. Yadav; Alexander N. Sennikov (Diversity, 2023)
The basal monocot genus Acorus comprises essential oil-producing plants widely used in traditional medicine in various countries, including India. Acorus calamus sensu lato is a polyploid complex where the essential oil composition, to some extent, depends on the ploidy level. The literature recognizes diploids (in temperate Asia and North America), triploids (Asian in origin, naturalized elsewhere) and tetraploids (temperate to tropical Asia) at the rank of varieties of A. calamus. We show that the current use of the name A. calamus var. angustatus for the tetraploids is not properly justified. The earliest name based on the Asian material is A. calamus var. verus published in 1753 by Linnaeus. We justify the use of the Linnaean variety for tetraploids by selecting an epitype based on the material cultivated in Peninsular India, for which direct chromosome counts are provided. The name A. verus is available if the tetraploid cytotype is recognized at the species rank. We support earlier data on the importance of leaf anatomy for cytotype diagnostics in Acorus, but also show the limitations of the use of this approach. The growth pattern of the tropical Indian tetraploid material is discussed, and the evergreen nature of the accession studied here is documented. The exact chromosome number of the tetraploid Acorus requires further clarification. All metaphase plates examined here showed at least 44 chromosomes, but plates apparently showing more than 44 chromosomes were found as well. They may be explained by technical difficulties in counting chromosomes in Acorus. Alternatively, our data may indicate the occurrence of aneuploid mixoploidy.